Komentar dan cadangan kajian semula terhadap Undang-Undang Pentadbiran Agama Islam - Shuaib, Farid Sufian (Penerbit IKIM, 2012)
The chapter looks at the history and development of of Islamic institution in Malaysia. The issues of federalism and distribution of legislative powers are discussed in relation to Islamic institution. The chapter discusses the Islamic religious councils, mufti and syariah courts.